2014
DOI: 10.1097/hco.0000000000000110
|View full text |Cite
|
Sign up to set email alerts
|

Facing the complexity of ischaemic heart disease with intracoronary pressure and flow measurements

Abstract: FFR, CFR and IMR have independently been shown to improve IHD risk stratification. Their combined use is feasible and appealing, and might lead to a more comprehensive invasive assessment of IHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…As a previous study showed that HSR is a better index of ischaemia than FFR,33 these data could suggest that FFR may fail to identify ischaemic lesions in a subset of patients with ACS in non-culprit lesions. Such findings are not surprising as dissociation between FFR and CFR has been previously demonstrated using combined evaluation of microvascular resistances, CFR and FFR in patients with SA and UA 5 34. Such discordance has been suggested to be due to clinically relevant coronary pathophysiology 35.…”
Section: Potential Limitations Of Ffr In Acsmentioning
confidence: 59%
See 1 more Smart Citation
“…As a previous study showed that HSR is a better index of ischaemia than FFR,33 these data could suggest that FFR may fail to identify ischaemic lesions in a subset of patients with ACS in non-culprit lesions. Such findings are not surprising as dissociation between FFR and CFR has been previously demonstrated using combined evaluation of microvascular resistances, CFR and FFR in patients with SA and UA 5 34. Such discordance has been suggested to be due to clinically relevant coronary pathophysiology 35.…”
Section: Potential Limitations Of Ffr In Acsmentioning
confidence: 59%
“…Thus, normal FFR value (>0.80) may indeed be falsely negative due to incomplete hyperaemia. This phenomenon may be true for both culprit and non-culprit lesions in ACS and is dependent on raised microvascular resistance and reduced coronary flow reserve (CFR) as recently summarised by Echavarría-Pinto et al 5 Importantly, the possibility of false-negative results of FFR is increased around the grey zone of FFR and values of FFR between 0.81 and 0.85 should be managed cautiously as a residual risk of events may be present. 6 The goal of this literature review is to summarise laboratory and recent clinical investigations concerning the use of FFR in culprit and non-culprit lesions in ACS mainly because these studies carry important implications both for treatment and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Angina may result from abnormalities in other compartments, and the same coronary wire used to measure FFR, may be simultaneously used to interrogate the microvasculature (by indicator-thermodilution) allowing a more complete assessment of a patient’s coronary physiology at the time of ICA, while providing prognostic data to guide management [88]. In addition to IMR and RRR, the assessment of coronary flow reserve (CFR) provide complementary information and can aid in the differentiation of a patient’s symptoms due to focal or diffuse epicardial disease, microvascular disease, or both [89]. Although the importance of reduced CFR (secondary to epicardial or microvascular disease) in defining adverse prognosis has been clearly demonstrated [90], the role and prognostic importance of the interrogation of the microvascular compartment alongside the epicardial vessel with FFR measurement is yet to be defined.…”
Section: Comprehensive Invasive Assessment Of Coronary Physiologymentioning
confidence: 99%
“…Combining FFR with CFR and IMR measurements in daily clinical practice can give clinicians instantaneous and complementary diagnostic information on epicardial CAD and microvascular function in the catheter laboratory (for reviews, 46 48 ; Figure 2 ). This approach may be particularly relevant in a subset of patients presenting with angina, non-invasive evidence of ischaemia, but no significant epicardial CAD (FFR > 0.80).…”
Section: Stenosis Morphology and Functional Significancementioning
confidence: 99%